Paleogeographic and paleoecological significance of Schachriomonia (Brachiopoda) from the Upper Ordovician of the Tarim Basin, Northwest China. (November 2019) - Sproat, Colin D.; Zhan, Renbin
Abstract: The atrypide brachiopod Schachriomonia is documented here for the first time from the upper Katian Hadabulaktag Formation on the northeastern edge of Tarim Basin in Northwest China. These shells are conspecific with the earlier reported Rhynchotrema pentagonia Fang in Liu and Fang, 1990 from the same region. This species is most similar to Schachriomonia parva Popov et al., 1999 described from the Upper Ordovician of the Chu-Ili and Chingiz terranes and less closely resembles species from North and South China, indicating a close paleogeographic connection between these plates and terranes and Tarim during the Late Ordovician. Its dominance at three horizons in the study area may indicate that this species was an opportunistic colonizer of the seafloor following ecological disruption, or alternatively that the larvae were substrate-selective. Variation in shell shape from a nearly circular shell outline with a dorsal sulcus and ventral fold in the smallest shells to a wider outline with a more reversed dorsal fold and ventral sulcus in the largest is an example of ontogenic development. This may have been an adaptation to accommodate the growing lophophore or development of gonads in the mantle cavity over the life of the brachiopod. A stronger tooth-socket connection in larger shells strengthened the hinge area to better withstand the stresses caused by the mass of a larger shell.